Les plantes comme liant actif entre la terre et le paysage. Trois projets artistiques d’Agnes Denes, de Lois Weinberger et de Mali Wu - Catherine Grout (Projets de Paysage, 2022)
In this article addressing the issues of the urban context, the landscape and the land, in situ artistic interventions by Agnes Denes, Lois Weinberger and Mali Wu are studied from an aesthetic perspective. The analysis of the approaches and of these projects focuses on ways of considering the soil, plants, and the act of planting, and on how they relate to several interpretations of the landscape. Plants are considered by these artists as a manifestation of nature, a vital energy, a focus on food, a symbolic force, as well as a means of establishing a connection to a cultural history, and to actions relating to the maintenance and reconsideration of urban daily life. They are also considered in terms of economic, symbolic and social values, and to the challenging and the renewal of these values. In addition, as statements these artistic interventions resonate with the perceptions of city dwellers and current ethical and ecological expectations, some of which are critical of the practice of soil levelling.